Applying Whispering Game in Developing Listening Comprehension of Grade Eleven Students of SMAN 7 Palu - Ewis Febriani; Sudarkam R. Mertosono; Desrin Lebagi; Mukrim, Mukrim (Universitas Cokroaminoto Palopo, 2024)
This purpose of this research is to investigate the effectiveness of using the whispering game in developing listening comprehension of grade eleven students of SMAN 7 Palu. This research applied a pre-experimental research approach. The population for this research was the eleventh grade students at SMAN 7 Palu, which consisted of ten classes, with 36 students picked from class XI 3 using purposive sampling. The instrument used in this research was a listening test with audio. Researchers employed pre-test and post-test methods to collect data. The collected data was analyzed using SPSS Version 23. The results showed that the mean score of the pre-test was (61.30) and post-test was (77.59). According to the findings of the t-test simple independence test, the sig (2 tailed) (0.000) value is lower than 0.05. This demonstrates that the alternative hypothesis is accepted. As a result, the whispering game is effective in developing listening comprehension of grade eleven students of SMAN 7 Palu.